METHODS FOR AMASSING DATA IN CROSS-CULTURAL PRAGMATICS RESEARCH - Le, Huu Loc (VNU Journal of Foreign Studies, 2024)
This article discusses prevalent and up-to-date data-amassing techniques for cross-cultural pragmatics studies. Based on the distinctive features of data types, the commonly used methods are outlined with their pluses and minuses, along with the author’s remarks and recommendations on how to employ them for fulfilling research purposes. Additionally, the paper suggests that an integration of the data-gathering methods proves to be of great value for pragmatics studies in general and cross-cultural pragmatics studies in particular, contributing to ensuring the validity and reliability of these kinds of research.